The Role of Indian Systems of Medicine and Homoeopathy (ISM &H) Policy 2002 in Revitalizing Ayurvedic and Homoeopathic Practices (Homoeopathy for All, 2024)
India has a millennium-old,  somewhat well-organized medical  system called Ayurveda. Additional  conventional systems that evolved a  bit later (yet no less old) are Unani,  Siddha, and Amichi. Additionally,  homeopathy is a very common  system in the nation. Even though  homoeopathy arrived in India in  the 18th century, it fully blended  into Indian society and developed  alongside other traditional systems,  which is why it is regarded as a  component of Indian systems of  medicine. As a result, India holds  the rare distinction of having  seven accepted medical systems:  homoeopathy, naturopathy, yoga,  siddha, unani, and ayurveda. These  systems are more commonly  referred to as AYUSH or ISM & H  (Indian systems of Medicine and  Homoeopathy). Indian medical  systems are unique in that they are  holistic in character. These systems  have endured for a very long  time. ISM systems are "culturally  compatible" and deeply ingrained  in people's belief systems. These  systems have substantial public  support.
Keywords: government; Health; prioritized